Chemokine Function in Periodontal Disease and Oral Cavity Cancer - Sahingur, Sinem Esra; Yeudall, W. Andrew (Frontiers in Immunology, 2015)
The chemotactic cytokines, or chemokines, comprise a superfamily of polypeptides with a wide range of activities that include recruitment of immune cells to sites of infection and inflammation, as well as stimulation of cell proliferation. As such, they function as antimicrobial molecules and play a central role in host defenses against pathogen challenge. However, their ability to recruit leukocytes and potentiate or prolong the inflammatory response may have profound implications for the progression of oral diseases such as chronic periodontitis, where tissue destruction may be widespread. Moreover, it is increasingly recognized that chronic inflammation is a key component of tumor progression. Interaction between cancer cells and their microenvironment is mediated in large part by secreted factors such as chemokines, and serves to enhance the malignant phenotype in oral and other cancers. In this article, we will outline the biological and biochemical mechanisms of chemokine action in host-microbiome interactions in periodontal disease and in oral cancer, and how these may overlap and contribute to pathogenesis.